2012
DOI: 10.1080/15205436.2011.642926
|View full text |Cite
|
Sign up to set email alerts
|

Do We Need to Go Cellular? Assessing Political Media Consumption Using a Single-Frame Landline/Cellular Survey Design

Abstract: Much research has been published on cellular phone only households and the challenges posed by cellular phones to traditional survey methodologies that attempt to generate representative samples using only landline telecommunications. This study reports analyses comparing two separate survey strata (N landline ¼ 152, N cellular ¼ 153) collected simultaneously and nested within a single-frame survey of a state in the American Midwest for differences in demographics, political orientations, individual difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, in 2008 and 2010, the response rates of landline samples differed from those of cellular samples. Hill, Tchernev, and Holbert (2012) found that although there were no differences in the mean education and income levels between landline and cellular samples, there were significant age and gender differences. In particular, participants in cellular samples tended to be younger than those in landline samples, and there was an oversampling of male participants in cellular samples and a majority of female participants in landline samples (Hill et al, 2012).…”
Section: Limitationsmentioning
confidence: 60%
“…Moreover, in 2008 and 2010, the response rates of landline samples differed from those of cellular samples. Hill, Tchernev, and Holbert (2012) found that although there were no differences in the mean education and income levels between landline and cellular samples, there were significant age and gender differences. In particular, participants in cellular samples tended to be younger than those in landline samples, and there was an oversampling of male participants in cellular samples and a majority of female participants in landline samples (Hill et al, 2012).…”
Section: Limitationsmentioning
confidence: 60%
“…Although the problems posed by CPO households for survey researchers have been well studied within political and health contexts, the issue has received almost no attention by mass communication researchers. The exception is a study by Hill and colleagues (2012) that examined differences in political media use between survey participants reached via landline versus survey participants reached by cell phone. (The study did not separate out CPO households.)…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, this study heeds Hill et al’s (2012) call for additional research exploring the implication of a growing number of CPO households for media consumption surveys. Understanding media use is important not only for understanding the changing preferences among audiences but also for understanding how individuals access information about topics like politics (Dahlgren, 2009; Graber, 2009; McLeod, Scheufele, & Moy, 1999) and health (Noar, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations